2021
DOI: 10.1049/ell2.12235
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of firing rhythms in a four‐stable memristor‐based Hindmarsh–Rose neuron

Abstract: This letter presents a novel locally active memristor with four-stable pinched hysteresis loops which has never been reported before. The non-volatile memory and local activity of the memristor are verified by the power-off plot and DC V-I plot. A memristive Hindmarsh-Rose (HR) neuron model is constructed by employing the proposed memristor to characterize the electromagnetic induction effect on the membrane potential. Co-existing multiple firing patterns are explored under different memristor initial states. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…It confirmed the existence of the fourth basic circuit element, that is memristor. The memristor have attracted the attention of many scholars for their potential applications in cellular neural network [2,3], associative and non-associative learning [4,5], circuit implemented electronic neurons [6], memory circuit [7], nonlinear oscillating circuits and other fields [8][9][10][11]. Because of the unique nonlinear characteristics of memristor, the chaotic circuit based on memristor has more abundant dynamic behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…It confirmed the existence of the fourth basic circuit element, that is memristor. The memristor have attracted the attention of many scholars for their potential applications in cellular neural network [2,3], associative and non-associative learning [4,5], circuit implemented electronic neurons [6], memory circuit [7], nonlinear oscillating circuits and other fields [8][9][10][11]. Because of the unique nonlinear characteristics of memristor, the chaotic circuit based on memristor has more abundant dynamic behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Lin et al constructed an HR neural network based on a tristable locally active memristor, and found that the proposed neural network produces three multi-stable phenomena with four different firing patterns simultaneously [33]. A model of HR neuron with four-stable locally active memristor as selfsynapses was proposed by Li et al and they found that four stable firing patterns in the proposed neuron can be switched freely by selecting appropriate initial conditions [34]. With further development of memristor research, locally active memristor has been extended to fractionalorder form, and the related research has been carried out.…”
Section: Introductionmentioning
confidence: 99%